FLOOD PREPAREDNESS OF ELDERLY LIVING IN WATERSHED, PENYARINGANVILLAGE, JEMBRANA, BALI - Pande Komang Sudiantika; Putu Ayu Sani Utami; Ni Luh Putu Eva Yanti (Program Studi Ilmu Keperawatan Universitas Jember, 2025)
Background: Preparedness is key to reducing post-disaster damage. The Elderly residing in watersheds are particularly vulnerable to floods. Objective: This study aimed to examine the demographic characteristics of older adults and their level of flood preparedness in the Banjar Anyar Kelod watershed. Methods: A descriptive quantitative design was used involving 161 older adults selected through purposive sampling. Participants completed 20 questions from the preparedness questionnaire. Data analysis used descriptive statistics (mean, minimum, maximum, and percentage) to describe the characteristics of the respondents. This study also conducted a bivariate analysis using the Chi-square test to determine the relationship between demographic variables (age, gender, education level, and occupation) and the preparedness level of older people. The relationship between variables was measured using Cramer's V to determine the strength of the relationship between variables. Results: The Preparedness of the elderly living in the watershed of Banjar Anyar Kelod was categorized as less prepared (55.10%). Education level showed a moderate and significant relationship with preparedness (x²(10) = 28.24, p = 0.0017; Cramer's V = 0.30),indicating that higher education is associated with better preparedness among older people. Occupation also showed a significant moderate relationship (x²(14) = 37.58, p = 0.0006; Cramer's V = 0.34). Conclusion: The village government, community health center (Puskesmas) officers, and the Regional Disaster Management Agency (BPBD) officers are expected to collaborate in facilitating flood preparedness training for the elderly.